Clinical Features and Histological Features of Relapsed Patients of Ulcerative Colitis - Khan, Momina Jehangir; Rehman, Amman ur; Sahrish, Fariha; Mukhtar, Rabia; Ilyas, Anum; Aamir, Zain (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Ulcerative colitis is a chronic inflammatory disease of indefinite etiology having relapsing and remitting course. Assessing inflammatory activity via different scoring systems along with clinical correlation plays an important role in the diagnosis and surveillance of ulcerative colitis patients. Histopathological findings should be correlated with the clinical, endoscopic and radiological findings to exclude other causes with similar symptomatology, hence improving the management of patients with UC. Aims and objective: To determine the clinical features and histological features in relapsed patients of ulcerative colitis. Place and duration of study: Department of Pathology, Histopathology section, Sheikh Zayed hospital Lahore, from 25th February, 2016 to 25th February, 2017. Materials and methods: One hundred and ninety cases underwent endoscopic colonic biopsies from the three sites proximal colon, distal colon and rectum. Results: Out of one hundred ninety patients majority patients presented with vague abdominal pain 105(55.3%) followed by bleeding per rectum 74(38.9%). Most commonly seen histological feature is cryptitis 189(99.5%) succeeding chronic inflammation 188 (98.9%). Conclusion: Relapsed patients predominantly presents with vague abdominal pain. Cryptitis is most commonly seen histological feature in relapsed patients of ulcerative colitis.